HTML5 multimedia developer's guide - Bluttman, Ken (McGraw Hill, 2012)
"Now you can create rich, interactive content in the browser and deploy it across all platforms. HTML5 Multimedia Developer's Guide shows you how. You'll learn to use the revolutionary new features of HTML5, including the native audio, video, and drawing elements that eliminate the need for third-party plug-ins. New tags, the simplified doctype, local data storage, drag-and-drop, and geolocation are also covered. Detailed code examples illustrate the techniques discussed. By the end of the book, you'll be able to develop amazing multimedia applications and websites with HTML5"--